2005
DOI: 10.1159/000087824
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Risk Factors of Amyloidogenesis in Familial Mediterranean Fever

Abstract: Background/Aims: Evaluation of the risk factors, and phenotype-genotype correlation of familial Mediterranean fever (FMF) gene (MEFV) and serum amyloid A1 (SAA1) gene polymorphisms in renal amyloidosis. Methods: We investigated MEFV and SAA1 genotypes (α, β, and γ isoforms) in 50 FMF patients and 50 healthy children. Tel-Hashomer criteria were used for the diagnosis and severity scoring of FMF. Results: The most common MEFV mutation and SAA1 genotype were M694V/M694V (n = 26/50) and SAA1 α/α (n = 26/50), respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 59 publications
2
13
1
1
Order By: Relevance
“…Other indirect findings suggesting the association between M694V and amyloidosis are; (1) homozygous M694V patients had higher disease severity scores (Erdağ et al, 2008;Inal et al, 2009;Pasa et al, 2008;Ureten et al, 2010); (2) the resistance to colchicine treatment was more common among homozygous M694V patients (Soylemezoglu et al, 2010); and (3) the M694V/M694V genotype was the most common cause of phenotype 2 disease. The clinical significance of variants other than M694V, M680I, M694I and V726A which were studied in all investigated studies (Akpolat et al, 2010;Albayrak, 2010;Atagunduz et al, 2004;Cakar et al, 2001;Delibaş et al, 2005;Duşunsel et al, 2008;Erdağ et al, 2008;Ertekin et al, 2005;Inal et al, 2009;Ozalkaya et al, 2011;Koksal et al, 2009;Mimouni et al, 2000;Pasa et al, 2008;Peru et al, 2008;Samli et al, 2006;Sayhan et al, 2000;Shohat et al, 1998;Solak et al, 2008;Soylemezoglu et al, 2010;Turkcapar et al, 2007;Ureten et al, 2010;Yalçinkaya et al, 2000;Yilmaz et al, 2001Yilmaz et al, , 2003Yigit et al, 2008) is still under discussion. In Table 2, there were 19 patients having one of these mutations/variants of whom 12 had only these mutations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other indirect findings suggesting the association between M694V and amyloidosis are; (1) homozygous M694V patients had higher disease severity scores (Erdağ et al, 2008;Inal et al, 2009;Pasa et al, 2008;Ureten et al, 2010); (2) the resistance to colchicine treatment was more common among homozygous M694V patients (Soylemezoglu et al, 2010); and (3) the M694V/M694V genotype was the most common cause of phenotype 2 disease. The clinical significance of variants other than M694V, M680I, M694I and V726A which were studied in all investigated studies (Akpolat et al, 2010;Albayrak, 2010;Atagunduz et al, 2004;Cakar et al, 2001;Delibaş et al, 2005;Duşunsel et al, 2008;Erdağ et al, 2008;Ertekin et al, 2005;Inal et al, 2009;Ozalkaya et al, 2011;Koksal et al, 2009;Mimouni et al, 2000;Pasa et al, 2008;Peru et al, 2008;Samli et al, 2006;Sayhan et al, 2000;Shohat et al, 1998;Solak et al, 2008;Soylemezoglu et al, 2010;Turkcapar et al, 2007;Ureten et al, 2010;Yalçinkaya et al, 2000;Yilmaz et al, 2001Yilmaz et al, , 2003Yigit et al, 2008) is still under discussion. In Table 2, there were 19 patients having one of these mutations/variants of whom 12 had only these mutations.…”
Section: Discussionmentioning
confidence: 99%
“…We analyzed twenty-seven papers (Akpolat et al, 2010;Albayrak, 2010;Atagunduz et al, 2004;Cakar et al, 2001;Delibaş et al, 2005;Duşunsel et al, 2008;Erdağ et al, 2008;Ertekin et al, 2005;Inal et al, 2009;Ozalkaya et al, 2011;Oztürk et al, 2008;Koksal et al, 2009;Mimouni et al, 2000;Pasa et al, 2008;Peru et al, 2008;Samli et al, 2006;Sayhan et al, 2000;Shohat et al, 1998Shohat et al, , 1999Solak et al, 2008;Soylemezoglu et al, 2010;Turkcapar et al, 2007;Ureten et al, 2010;Yalçinkaya et al, 2000;Yilmaz et al, 2001;Yilmaz et al, 2003;Yigit et al, 2008) from 20 centers located in 11 different cities and including 3505 subjects (400 with amyloidosis and 3105 without amyloidosis). The data of one center (Center 20) which did not publish their cases separately was obtained from an international study (Mimouni et al, 2000) (online Supplementary data).…”
Section: Description Of the Datamentioning
confidence: 99%
“…Amyloidosis occurs less frequently in the presence of mutations other than p.Met694Val. 6,40 -42 Some studies have also found that p.Met694Val is also associated with a generally more severe form of the disease, [43][44][45] but other studies have not confirmed this. 46 One study found that p.Met694Val was not associated with increased severity of the disease but was significantly associated with amyloidosis.…”
Section: Genotype-phenotype Correlationsmentioning
confidence: 99%
“…[11][12][13][14] Recent studies show that FMF and SAA1:1 genotype are associated with amyloidosis. 15 In the majority of people, acute phase AA amyloid proteins are encoded by polymorphic SAA1 gene that shows variation in different ethnic groups. 13,14 Two single nucleotide polymorphisms were reported in exon 3 (codon 2995 C5T and codon 3010 C4T) of SAA1 gene.…”
Section: Introductionmentioning
confidence: 99%